A new species of Lusius Tosquinet (Hymenoptera, Ichneumonidae, Ichneumoninae) from China, with a key to Chinese species - Han, Yuan-Yuan; Chen, Meng-Meng; Dong, Yan (Zootaxa, 2024)
A new species of Lusius Tosquinet, 1903, L. hunanensis sp. nov., from Hunan province of China, is described and illustrated. The new species is characterized by clypeus nearly smooth, truncated laterally, rounded medially; mesopleuron entirely punctate; propodeum weakly rugose with transverse striation, without punctures; postpetiole yellow, metasomal tergite 2 and tergite 3 with small spot laterally. A key to Chinese species of Lusius is provided.